Competence, Motivation And Facilities And Infrastructure As Determining Factors In Dpmptsp Employee Performance - Tien Yus Tini; Yessy Novianty (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to analyze and prove the influence of competence, motivation, facilities and infrastructure on employee performance to support the success of socialization at the Investment and One-Stop Integrated Service Office (DPMPTSP) in Ogan Komering Ilir Regency. This study is a quantitative study, the population in this study were 115 DPMPTSP employees and the sampling method was saturated sampling. The results of this study indicate that partially competence has a negative and significant effect on employee performance, while motivation, facilities and infrastructure have a significant positive effect on performance. Simultaneously, the variables of competence, motivation, facilities and infrastructure have a positive and significant effect on the performance of DMPTSP employees.